(untitled) (Journal of Business Management and Accounting, 2019)
Islamic banking institutions are different from their conventional counterparts as they incorporate religious and spiritual values in their operations. Despite this significant difference, few studies have investigated this spiritual aspect especially from the perspective of the brand. The main purpose of this study is to develop a valid and reliable scale to measure the spiritual brand attribute of Islamic banks. Based on the result of the interviews and review of literature, 28 items were proposed and analysed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). A total of 14 items remain on the final scale classified in three dimensions which are beliefs, ethics, and corporate social responsibility (CSR). The new brand attribute scale is different from the existing scale as it focuses mainly on the spiritual and religious aspect incorporated into the Islamic banking brand.